River tourism / [Edited by] B Prideaux, Malcolm Cooper - Prideaux, Bruceedited
This book explores river tourism from a range of perspectives including river uses, heritage, management, environmental concerns, and marketing. The book has 15 chapters and an index. The intended readership includes researchers and students of leisure and tourism.